Anthropometric, body composition and physical fitness among primary school children / Nur Ashikin Ahmed Zaki - Ahmed Zaki, Nur Ashikin (2013)
The aim of this study was to analyze the association between body composition and physical fitness among primary schoolchildren in Beruas, Perak. A total of 246 participants, aged from 10 to 12 years old were randomly selected from four primary schools. Anthropometric and body composition were assessed. The mean body mass index (BMI) of boys (n=l 13) and girls (n=133) were 19.09±5.03 and 18.49±4.69, respectively. The prevalence of underweight, normal weight, overweight and obese was at 24.8%, 48.8%, 13.4% and 13.0%, respectively. Physical fitness comparison by weight categories, noted that the normal weight category showed significantly better performance than the other weight categories (p<0.05). Comparison by age revealed that, the 12 years old group performed significantly better than the other age groups (p<0.05). The Partial Correlation analysis revealed a negative correlation with high significant correlation between (BMI, r=0.58), waist circumference (WC, r=0.60), and percentages body fat (BF, r=0.59) among overweight/obese female category for upper body strength (UBS). Result also showed high significance between (WC) and (UBS) for boy in the underweight category (r=0.66) and girl in the normal weight category (r=0.53). Only BF (r=0.52) were correlated with UBS in boy with normal weight category. Moreover, only UBS for girl in normal weight category was highly correlated with WC (r=0.52). In conclusion, malnutrition either for the underweight or for overweight among primary school children in Beruas, Perak were significantly associated with physical fitness level.